Measuring stock market integration during the Gold Standard - Rebecca Stuart (University of Neuchâtel, Institute of Economic Research (IRENE), 2020)
This paper uses a broad geographical sample to investigate stock market integration during the classical Gold Standard. It is novel in estimating 'global components' of stock market returns, using methods proposed by Volosovych (2011), Pukthuanthong and Roll (2009) and Ciccarelli and Mojon (2010). Contrary to the existing literature, all three measures suggest that integration increased during the first decades of the Gold Standard before levelling off thereafter. However, a comparison with more recent data suggests the level of integration was low compared to today. The results are robust to alternative formulations of the global component and alternative measures of returns.
Keywords: G1; N2; 330; stock returns; principal components analysis; Gold Standard